2015
DOI: 10.1128/jvi.02318-14
|View full text |Cite
|
Sign up to set email alerts
|

White Spot Syndrome Virus Protein Kinase 1 Defeats the Host Cell's Iron-Withholding Defense Mechanism by Interacting with Host Ferritin

Abstract: We show here that white spot syndrome virus (WSSV) ensures the availability of iron by using a previously unreported mechanism to defeat the host cell's iron-withholding defense mechanism. This defense is often implemented by ferritin, which can bind up to 4,500 iron atoms and acts to sequester free iron within the cell. WSSV's novel counterstrategy is mediated by a direct protein-protein interaction between viral protein kinase 1 (PK1) and host ferritin. PK1 interacts with both ferritin and apoferritin, suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Additionally, Nipah virus matrix protein inhibits the host IB kinase epsilon (IKK) kinase-mediated IFN type I antiviral response by targeting the host E3-ubiquitin ligase TRIM6 (45). A recent study revealed that the WSSV genome can encode protein kinase 1 to defeat the host cell's iron-withholding defense mechanism by interacting with host ferritin (46). In this context, viruses possess complicated mechanisms to escape the host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Nipah virus matrix protein inhibits the host IB kinase epsilon (IKK) kinase-mediated IFN type I antiviral response by targeting the host E3-ubiquitin ligase TRIM6 (45). A recent study revealed that the WSSV genome can encode protein kinase 1 to defeat the host cell's iron-withholding defense mechanism by interacting with host ferritin (46). In this context, viruses possess complicated mechanisms to escape the host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this, hosts have evolved mechanisms through which they can withhold iron from pathogens, thereby inhibiting their proliferation. The protein responsible for this mechanism is ferritin [ 105 ]. The ferritin defense mechanism has been demonstrated in L. vannamei , where its injection reduced susceptibility to WSSV infection.…”
Section: Wssv Infectionmentioning
confidence: 99%
“…Conversely, dsRNA-mediated knockdown of ferritin resulted in a three-fold increase in viral copy number [ 165 ]. Through the use of a yeast two-hybrid experiment, it has been shown that WSSV protein kinase 1 (WSSV PK1) can interact with host ferritin and influence the availability of iron [ 105 ]. Binding of WSSV PK1 does not release iron from ferritin but rather prevents iron from binding to apoferritin (ferritin without bound iron).…”
Section: Wssv Infectionmentioning
confidence: 99%
“…Protein kinase 1 of WSSV interacts with shrimp ferritin and prevents it from iron loading, and thus stabilizes the cellular labile iron pool. This may be an assault mechanism of WSSV to counteract the host cell's iron-withholding defense mechanism [50]. Ferritin synthesis has been reported to be increased in mengovirusinfected cells to combat with the increased levels of free iron after virus infection [51].…”
Section: Discussionmentioning
confidence: 99%